Study on Rivers Pollution and Water Quality in DKI Jakarta - Koto, J; Negara, Ridho Bela (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
As many other cities in the world, DKI Jakarta faces serious problems in the flood. In rainy season, common flooding is caused by several factors as follows: lowland areas in the northern part of Jakarta below sea level, urbanization rate, irregular population density, river pollution, slum neighborhood where scattered rubbish where quickly provoke the flood to stagnate and increase rather than receding. This paper studied on rivers pollution in DKI Jakarta. It was founded that water quality from 13 rivers in DKI Jakarta was at a critical level. The lack of sanitation systems in residential areas around rivers has highly contributed to pollute the rivers. It was 96 percent of the water is badly polluted. Therefore river water in DKI Jakarta can be harmful to health if consumed by the community.